Axonal spectrins: All-purpose fences - Eshed-Eisenbach, Yael (The Rockefeller University Press, 2013)
A membrane barrier important for assembly of the nodes of Ranvier is found at the paranodal junction. This junction is comprised of axonal and glial adhesion molecules linked to the axonal actin–spectrin membrane cytoskeleton through specific adaptors. In this issue, Zhang et al. (2013. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201308116) show that axonal βII spectrin maintains the diffusion barrier at the paranodal junction. Thus, βII spectrin serves to compartmentalize the membrane of myelinated axons at specific locations that are determined either intrinsically (i.e., at the axonal initial segment), or by axoglial contacts (i.e., at the paranodal junction).